2018
DOI: 10.1007/s10935-018-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of New Immigrants Into a Randomized Controlled Prevention Trial: The Live Well Experience

Abstract: Minority populations are hard to reach with prevention interventions because of cultural and logistical barriers to recruitment. Understanding how to overcome these barriers is pertinent to reducing the elevated burden of obesity within these underserved communities. To inform this literature gap, we explore the processes and outcomes of recruitment for Live Well-a randomized controlled obesity prevention intervention targeting new immigrant mothers and children from Brazil, Latin America, and Haiti who were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…In addition to bilingual capacity and cultural knowledge, the e-CHECC-up team mobilized ethnic churches as the main setting for direct recruitment. Faith-based organizations serve as epicenters for social, religious, and health promotion activities across diverse racial and ethnic minority and immigrant communities, including African American, Hispanic, and Asian Americans [ 33 , 36 , 42 , 43 ]. Building upon existing community strengths and resources, faith-based organizations are well-suited community partners for health research and for long-term and sustainable collaboration [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bilingual capacity and cultural knowledge, the e-CHECC-up team mobilized ethnic churches as the main setting for direct recruitment. Faith-based organizations serve as epicenters for social, religious, and health promotion activities across diverse racial and ethnic minority and immigrant communities, including African American, Hispanic, and Asian Americans [ 33 , 36 , 42 , 43 ]. Building upon existing community strengths and resources, faith-based organizations are well-suited community partners for health research and for long-term and sustainable collaboration [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 26 records included in this review varied in research objectives and study designs. Four studies were randomized clinical trials involving only quantitative evaluation of recruitment (with the review of study records to evaluate recruitment and/or surveys or questionnaires about recruitment) 25–28 . Seven were qualitative studies (which included interviews or focus groups with potential participants to inform a future clinical trial) 29–35 .…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies questioned parents and children about the facilitators and/or barriers to engaging in clinical trials, 29–33,41–49,52 and within these, only three studies assessed perceptions of both parents and children 47,48,52 . Also, 15 studies questioned research staff 25–28,34–40,44,46,50,51 . From all of these studies, two questioned children and parents and also researchers 44,46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though ethnic minorities are often underrepresented in health research [33], some studies have shown effective methods to recruit immigrant participants. Namely, by providing bilingual program information, and by facilitating partnerships with community organizations, recruitment of immigrant participants could be improved [34,35]. Future implementation studies should take into account these methods in the planning of their interventions.…”
Section: Discussionmentioning
confidence: 99%